Naval families, war and duty in britain, 1740-1820. - Gill, Ellen (Boydell Press, 2016)
"This book explores the competing demands of family, war and duty in the lives of eighteenth-century naval men and their families. It covers not just the men afloat and their wives ashore, but also the rich and complex financial, professional and fraternal networks that were essential to naval lives. By drawing on a substantial body of personal correspondence, the book goes beyond cultural and gendered stereotypes to examine the roles and responsibilities of men, women and children within a naval family and how war shaped and determined those roles. The families considered include those of several famous naval figures, including Philip Broke, Matthew Flinders and George Bass, and also the families of "lower deck" seamen, some of whom could not write for themselves and where data has been gleaned from previously unexplored petitions. The information provided contributes to a wider understanding of gender roles, especially masculinity, in the period and to eighteenth-century social and cultural history more broadly. Moreover, as insights into the intimate and emotional details of family life, especially between husbands and wives, are difficult to discover in any historical period (such intimacy being rarely recorded), the details presented here constitute a rare resource."